Content Analysis of Chhattisgarh Based Newspapers in Special Reference to Science & Technology Beat - Dr. Trishu Sharma (International Journal of Research in Informative Science Application & Techniques (IJRISAT), 2022)
The emergence of science and technology communication is generally attributed to the invention and dissemination of the information about fire churning technology. The objective of the study was to find out the coverage and space given to scientific and technological information in newspapers of Chhattisgarh. The result indicates that science gets very little space in newspapers and English newspapers cover science more prominently than Hindi newspapers. It also reveals that the health is the most preferred topic in Indian newspapers followed by environment. However, news is the most favored format for disseminating scientific information in Indian print media.